Decentralizability of efficient allocations with heterogenous forecasts - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2023)
Do price forecasts of rational economic agents need to coincide in perfectly competitive complete markets? To address this question, we define an efficient temporary equilibrium (ETE) within the framework of a two period economy. Although an ETE allocation is intertemporally efficient and is obtained by perfect competition, it can arise without the agents forecasts being completely coordinated on a perfect foresight price. Nevertheless, it entails price forecasts delicately related with each other: we show that regardless of the number of agents, there is a one dimensional set of such Pareto efficient allocations for generic endowments.